FREQUENCY OF RECURRENCE OF CERVICAL LESIONS IN PERSISTENT PAPILLOMAVIRUS INFECTION - Zaripova , Sh.X.; Asatova , M.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Cervical cancer remains a serious public health problem in Uzbekistan, ranking 2nd among the most common types of cancer. In the pilot districts of the Republic of Karakalpakstan in 2021-2022, in the first round of the pilot project, 3,303 HPV-positive women aged 30-55 years were identified during primary testing out of 49,002, who were retested in 2023-2024. The aim of the study was to determine the frequency of HPV persistence and relapses in HPV-positive women. The study was conducted on the Cepheid GeneXpert system using the polymerase chain reaction method, where the DNA of the human papillomavirus was determined. Repeated HPV testing covered 2862 women, which amounted to 88.1%, and 961 of them were found to have persistent HPV infection (33.6%). Triage coverage was 91.8% (882 women). Precancerous lesions of the cervix were detected in 19.8% (CIN 2/3), 2.9% of women were diagnosed with early-stage cervical cancer: non-invasive cervical cancer (CIS) in 2.2%, cervical cancer in 0.7% of women. Thus, the persistence of oncogenic HPV types is the cause of relapses of CIN 2+ and/or cervical cancer. The analysis of the conducted retesting for oncogenic HPV types of treated women indicates the need for mandatory monitoring of HPV-positive women for early detection of relapse of precancer and early stages of cervical cancer.